KEWAJIBAN ASURANSI JIWA KREDIT BAGI LESSEE DALAM PERJANJIAN SEWA GUNA USAHA: Life Insurance Requirement In Finance Lease Agreement - Wijaya, Geraldo Valento; Nurbaiti, Siti (AMICUS CURIAE, 2025)
Insurance is a risk transfer agreement that is often used by society to this day, and is also used by leasing companies to reduce the risk of default that may occur in leasing financing activities. However, leasing companies often require prospective financing recipients to insure their lives. Is there an obligation for life insurance for the lessee in the main lease agreement? This is the core issue that will be addressed. This research uses a normative type with a descriptive nature, by qualitatively analyzing secondary data including primary legal materials and secondary legal materials directly related to insurance law and financing law obtained through visits to the Trisakti University Faculty of Law Library and internet searches. Credit life insurance is categorized as voluntary insurance that prioritizes the agreement of the parties in concluding the insurance, so the insurance obligation stipulated in a Lease Agreement is a mistake against the fulfillment of the halal causa requirement and the principle of freedom of contract, which results in the Lease Agreement being null and void by law, and the lessee is not required to have life insurance. The Leasing Company (lessor) can only offer the prospective lessee the option to choose credit life insurance or not.